Optimal federal transfers during uncoordinated response to a pandemic. (1st November 2021) - Rothert, Jacek
Abstract: An outbreak of a deadly disease pushes policymakers to depress economic activity due to externalities associated with individual behavior. Sometimes, these decisions are left to local authorities (e.g., states). This creates another externality, as the outbreak doesn't respect states' boundaries. A strategic Pigouvian subsidy that rewards states which depress their economies more than the average corrects that externality by creating a race‐to‐the‐bottom type of response. In a symmetric equilibrium nobody receives a subsidy, but the allocation is efficient. If states are concerned about unequal burden of the lockdown costs, but cannot easily issue new debt to finance transfer payments, then lock‐downs will be insufficient in some areas and excessive in others. When that's the case, federal stimulus checks can limit the extent of local outbreaks.